Profile of Elementary Students Science-Related Attitudes In Mataram, Indonesia - Rindu Rahmatiah; Joni Rokhmat; A. Wahab Jufri; Gunawan; AA Sukarso (International Journal of Contextual Science Education, 2024)
This research is a continuation of previous research by the authors. The modified TOSRA (Test of Science-Related Attitudes), originally developed by Barry J. Fraser in 1987 for secondary high school students, has been validated in the previous research to be suitable for elementary school students in Mataram. This research aims to obtain an initial profile of science-related attitudes of grade 5 elementary school students in Mataram generally, based on gender and based on the school. This research aims to identify students’ science-related attitudes in four indicators: attitude to scientific inquiry, adoption of scientific attitudes, enjoyment of science lessons, and leisure interests in science. This descriptive ex post facto study explores the science-related attitudes of 318 students from 3 elementary schools in Mataram, Indonesia. The results revealed that there is a difference in indicator attitude to scientific inquiry. Still, there is no difference in the adoption of scientific attitudes, enjoyment of science lessons, and leisure interests in science between the students in these schools, and no significant differences in results based on gender overall.